2020
DOI: 10.1002/nme.6452
|View full text |Cite
|
Sign up to set email alerts
|

Error estimation for proper generalized decomposition solutions: A dual approach

Abstract: Summary The proper generalized decomposition is a well‐established reduced order method, used to efficiently obtain approximate solutions of multi‐dimensional problems in a procedure that controls the effects of the “curse of dimensionality.” The question of assessing the quality of the solutions obtained and adapting the approximations assumed, for example, the finite element meshes used, so that the best result is obtained at minimal cost, remains a relevant challenge. This article deals with finite element … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…Several applications using a more complex geometry, in the context of adaptivity driven by the global error, can be found in a previous paper. 29 The PGD solutions obtained are always converged in terms of number of modes, in order to consider only the errors sources coming from the mesh.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several applications using a more complex geometry, in the context of adaptivity driven by the global error, can be found in a previous paper. 29 The PGD solutions obtained are always converged in terms of number of modes, in order to consider only the errors sources coming from the mesh.…”
Section: Resultsmentioning
confidence: 99%
“…A more detailed explanation on the stopping criteria used can be found in our previous work on global adaptivity for PGD solutions. 29 The parametric domain, unless otherwise stated, has n h = 50 points. The tolerance for the PGD model, the fixed point iteration and the adaptivity process are all set to 10 −4 .…”
Section: Resultsmentioning
confidence: 99%
“…Additional work is being done to extend the results obtained to a 2D and 3D framework [13]. We can also extend the results to obtain quantities of interest and bounds of their errors from for the PGD approximations [14], giving a direct physical meaning to the solutions obtained.…”
Section: Resultsmentioning
confidence: 99%
“…This technique was developed specifically for the application of the hybrid equilibrium formulation, 4 in the context of determining bounds of the error of the solutions obtained from reduced order models 10 . The characteristic of hybrid equilibrium elements are well documented, and a comprehensive study of the convergence of these elements applied to 3D elasticity problems can be found in Reference 11.…”
Section: Introductionmentioning
confidence: 99%